2017
DOI: 10.1055/s-0037-1612640
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Clinical Risk Assessment Tool for 6-Week Postpartum Visit Nonadherence

Abstract: This risk assessment tool relies on routinely collected data, making its implementation simple. Applying it in the clinical setting allows for early, targeted intervention aimed at minimizing 6WPP nonadherence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…Despite its importance, attendance at postpartum visits varies from 5.7% to 95.4% completion. 26,31 Rates are especially low among individuals of minoritized racial and ethnic groups or those with limited resources, 32,33 despite the disproportionate risk of T2D and CVD. [34][35][36] In addition, individuals with suboptimal prenatal care utilization are less likely to receive postpartum blood pressure screening, 37 suggesting that those with decreased access to prenatal care are less likely to remain engaged in the health care system, compounding existing disparities.…”
Section: Barriers To Postpartum and Long-term Health Care After A Pre...mentioning
confidence: 99%
“…Despite its importance, attendance at postpartum visits varies from 5.7% to 95.4% completion. 26,31 Rates are especially low among individuals of minoritized racial and ethnic groups or those with limited resources, 32,33 despite the disproportionate risk of T2D and CVD. [34][35][36] In addition, individuals with suboptimal prenatal care utilization are less likely to receive postpartum blood pressure screening, 37 suggesting that those with decreased access to prenatal care are less likely to remain engaged in the health care system, compounding existing disparities.…”
Section: Barriers To Postpartum and Long-term Health Care After A Pre...mentioning
confidence: 99%
“…A prior publication simplified beta coefficients into points, therefore losing some precision in the risk estimation. 22 Finally, another advantage of our tool is the ability for easy precise calculations using an online calculator.…”
Section: Model Evaluationmentioning
confidence: 99%
“…The mean (SD) age of the sample was 27 (7.08) years, 40% were married or partnered, and 24% reported being employed. Patients in our sample entered into prenatal care on average at 14 (range, [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] weeks with an average of 10 (range, 5-15) prenatal visits. Using the Kotelchuck index reference described above, 29 41% of patients received inadequate care, 17% received intermediate care, 30% received adequate care, and 12% received adequate plus care.…”
Section: Cohort Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…2 Furthermore, these challenges are particularly acute for women without childcare assistance or who are struggling with social or economic instability. 3 Understanding both the importance and the unique challenges of postpartum care is critical as trends in maternal morbidity continue to rise with a concomitant increase in postpartum complications and hospital readmissions. Research has demonstrated increased postpartum readmission rates from 1.72% in 2004 to 2.16% in 2011.…”
mentioning
confidence: 99%